The Economic Implications of Case-Mix Medicaid Reimbursement for Nursing Home Care - David C. Grabowski (SAGE Publishing, 2002)
In recent years, there has been large growth in the nursing home industry in the use of case-mix adjusted Medicaid payment systems that employ resident characteristics to predict the relative use of resources in setting payment levels. Little attention has been paid to the access and quality incentives that these systems provide in the presence of excess demand conditions due to certificate-of-need (CON) and construction moratoria. Using 1991 to 1998 panel data for all certified U.S. nursing homes, a fixed-effects model indicates that adoption of a case-mix payment system led to increased access for more dependent residents, but the effect was modified in excess demand markets. Quality remained relatively stable with the introduction of case-mix reimbursement, regardless of the presence of excess demand conditions. These results suggest that CON and construction moratoria are still important barriers within the nursing home market, and recent quality assurance activities related to the introduction of case-mix payment systems may have been effective.